2000
DOI: 10.1046/j.1537-2995.2000.40111290.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion to blood group A and O patients of group B RBCs that have been enzymatically converted to group O

Abstract: ECO RBCs were comparable to group O cells for safety and efficacy in this study. The clinical significance of the increase in anti-B and of occasional serologic incompatibilities with ECO RBCs is unclear. If strategies can be developed to remove A epitopes, enzymatic conversion could be used to create a universal (group O) donor blood supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…54 In a more biomedical context, GLA has application in blood transfusion by removing the immunodominant a-1,3-linked galactose residues from group B red blood cells. 55,56 Enzymatic conversion of group B red blood cells using purified or recombinant coffee bean GLA has been achieved, 57,58 but the high amounts of enzyme needed constituted an economic obstacle for routine use in blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…54 In a more biomedical context, GLA has application in blood transfusion by removing the immunodominant a-1,3-linked galactose residues from group B red blood cells. 55,56 Enzymatic conversion of group B red blood cells using purified or recombinant coffee bean GLA has been achieved, 57,58 but the high amounts of enzyme needed constituted an economic obstacle for routine use in blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed by biochemical results (Liu et al, 2007) which verify that A and B antigens carried by both glycoproteins and glycolipids closer to the membrane are effectively digested, even if trace amounts can be detected with extremely sensitive methodology. These data are promising in the light of B-ECO RBCs generated with the older coffee bean process which survived and recovered normally in group O subjects (Kruskall et al, 2000) despite carrying minimal levels of remaining B antigen.…”
Section: Development Of the Eco Process And Characterization Of The Ementioning
confidence: 84%
“…A successful phase II cross-over clinical trial in patients was reported in 2000 (Kruskall et al, 2000). (Kruskall et al, 2000). The cross-match results obtained with the new A-ECO and B-ECO RBCs are similar and positive reactions can be found, mainly with group O sera and to a lesser extent with group B.…”
Section: Clinical Experience With Eco Rbcsmentioning
confidence: 95%
See 2 more Smart Citations